2019
DOI: 10.3390/molecules24183329
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of IR and NMR Spectral Changes Induced by Sigma-Hole Hydrogen, Halogen, Chalcogen, Pnicogen, and Tetrel Bonds in a Model Protein Environment

Abstract: Various types of σ-hole bond complexes were formed with FX, HFY, H2FZ, and H3FT (X = Cl, Br, I; Y = S, Se, Te; Z = P, As, Sb; T = Si, Ge, Sn) as Lewis acid. In order to examine their interactions with a protein, N-methylacetamide (NMA), a model of the peptide linkage was used as the base. These noncovalent bonds were compared by computational means with H-bonds formed by NMA with XH molecules (X = F, Cl, Br, I). In all cases, the A–F bond, which lies opposite the base and is responsible for the σ-hole on the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 81 publications
2
34
1
Order By: Relevance
“…[37][38][39][40][41][42] Computational study of the pnictogen bonding An oen suggested prerequisite for strong PnBs, following studies on halogen and chalcogen bonding, is the presence of large V max (maximum in the electrostatic potential energy surface calculated on a molecular surface at 0.001 au) 43,44 values associated with the electrophilic regions of the ESP surface. 40,[45][46][47][48] A typical design strategy used to achieve this is to incorporate polar primary bonds. The replacement of O with S to enhance the stability of the primary bonds is therefore expected to result in smaller V max values and weaker PnBs.…”
Section: In Situ Encapsulation Of Guest Moleculesmentioning
confidence: 99%
“…[37][38][39][40][41][42] Computational study of the pnictogen bonding An oen suggested prerequisite for strong PnBs, following studies on halogen and chalcogen bonding, is the presence of large V max (maximum in the electrostatic potential energy surface calculated on a molecular surface at 0.001 au) 43,44 values associated with the electrophilic regions of the ESP surface. 40,[45][46][47][48] A typical design strategy used to achieve this is to incorporate polar primary bonds. The replacement of O with S to enhance the stability of the primary bonds is therefore expected to result in smaller V max values and weaker PnBs.…”
Section: In Situ Encapsulation Of Guest Moleculesmentioning
confidence: 99%
“…Noncovalent interactions allow our world to exist. Their specific interaction energies [ 1 , 2 , 3 , 4 ], their effect on the spectral [ 5 , 6 , 7 ], chemical [ 8 , 9 ], and structural [ 10 , 11 , 12 ] properties of individual molecules, those in adducts and solutions [ 13 , 14 , 15 ], have been and remain vital to the progress of chemistry. The interpretation of spectral shifts caused by changes in the properties of a particular interaction can be carried out in sufficient detail [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…5-Nitro-2-furaldehyde semicarbazone (3β) and 5-nitro-2-thiophene semicarbazone (4) were synthesized by the same procedure, only semicarbazide hydrochloride (1 mmnol) was used instead of thiosemicarbazide. Solid samples of the synthesized compounds (1)(2)(3)(4) were dissolved in a pure solvent (MeOH, EtOH, i-PrOH, MeCN, or dmf) or solvent mixture (dmf + MeOH, dmf + EtOH, dmf + i-PrOH, dmf + MeCN, or MeOH + MeCN; 1 + 1 v/v in all cases) and heated for 10 minutes and then left for crystallization under ambient conditions (in covered, but not sealed, vessels to allow for the decelerated evaporation of solvents). Further structurally different crystalline products were obtained by the slow evaporation of solvents only for 1 and 3 (i.e., 5-nitro-2-furaldehyde thiosemicarbazone dimethylformamide dimethylformamide solvate (1·dmfα, by slow evaporation from dmf solution), 5-nitro-2-furaldehyde thiosemicarbazone dimethylformamide solvate (1·dmfβ, by slow evaporation from MeOH:dmf (1:1 v/v) solvent mixture), and 5-nitro-2-furaldehyde semicarbazone (3γ, by slow evaporation from MeOH:MeCN (1:1 v/v) solvent mixture as well as from pure MeCN)).…”
Section: Synthesismentioning
confidence: 99%
“…Knowledge about non-covalent interactions increases with each passing year [1][2][3][4][5], but is still insufficient to enable the complete design and prediction of the crystal structure of organic compounds, even with the usage of computational crystal structure prediction. Application of computational methods allows for the prognostication of crystal packing on the basis of the structural formula, but these methods still lead to ambiguous results or give an incorrect build of the crystal net in some cases [6,7].…”
Section: Introductionmentioning
confidence: 99%